Pengaruh Pemberian Oksigen Hiperbarik Terhadap Diameter Calluspada Tikus Model Fraktur Diafisis Tulang Femur - SATRIOAJI, ABDILLAH MAULANA; ROFIQ, AKHMAD; MAYO DAGRADI, ERIC (Hang Tuah Medical Journal, 2023)
Background : Fracture is a condition where the bone is cut off due to significant pressure which can be in the form of bending, twisting, or pulling due to trauma, work accidents, traffic accidents, as well as degeneration and pathological processes. Fractures can result in loss of productivity and individual disability. One of the adjuvant therapies to accelerate the bone healing process in patients with fractures is hyperbaric oxygen therapy.   Objective : The purpose of this study was to determine the effect of HBO therapy on the diameter of the callus formed in a rat model of fracture of the diaphysis of the femur.   Methods : This research is an experimental study using a post test only control group design. The object of this study is a rat fracture model with HBO therapy as the independent variable and a fracture model without HBO therapy as a control variable.   Results : The results of this study showed the effect of HBO therapy on increasing the diameter of the callus formed in the fracture of the rat model   Conclusion : There was a significant difference in the diameter of the callus formed in fracture model mice treated with HBO compared to those not treated with HBO.   Keywords : HBO therapy, Fracture, Callus, Wistar Rat